Dietary flaxseed oil and vitamin E improve semen quality via propionic acid metabolism - Yuan, Chongshan; Zhang, Kaiyan; Wang, Zhe; Ma, Xin; Liu, Hongyu; Zhao, Jing; Lu, Wenfa; Wang, Jun (Frontiers in Endocrinology, 2023)
The present study investigated the effects of dietary supplementation with flaxseed oil (FO) and/or vitamin E (VE) on semen quality. 16 fertile Simmental bulls were selected and randomly divided into 4 groups (n = 4): the control group (control diet), FO group (control diet containing 24 g/kg FO), VE group (control diet containing 150 mg/kg VE) and FOVE group (control diet containing 150 mg/kg VE and 24 g/kg FO), and the trial lasted 10 weeks. The results showed that the addition of FO independently can increase sperm motion parameters, the levels of catalase (CAT), glutathione peroxidase (GSH-Px), testosterone (T) and estradiol (E2), while reduce oxidative stress in seminal plasma (P < 0.05). Supplement of VE independently can increased the motility, motility parameters, CAT and superoxide dismutase (SOD) levels, and reduce oxidative stress in seminal plasma (P < 0.05). There was an interaction effect of FO × VE on motility and reactive oxygen species (ROS), while GSH-Px and ROS were affected by week × VE 2-way interaction, levels of T and E2 were also affected by the dietary FO × week interaction (P < 0.05). The triple interaction effects of FO, VE and week were significant for malondialdehyde (MDA) (P < 0.05). Compared with the control group, sperm from the FOVE group had a significantly higher in vitro fertilization (IVF) rate, and subsequent embryos had increased developmental ability with reduced ROS levels at the eight-cell stage, then increased adenosine triphosphate (ATP) content and gene expression levels of CAT, CDX2, Nanog, and SOD at the blastocyst stage (P < 0.05). Metabolomic and transcriptomic results indicated that dietary supplementation of FO and VE increased the expression of the metabolite aconitic acid, as well as the expression of ABAT and AHDHA genes. With in-silico analysis, it can be concluded that the effects of dietary FO and VE on improving semen quality and embryo development may be related to increased aconitic acid via the ABAT and AHDHA genes involved in the propionic acid metabolism pathway.